2017
DOI: 10.1097/mph.0000000000000793
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Tunisian Patients With Acute Lymphoblastic Leukemia and Its Involvement in Leukemic Relapse

Abstract: The aim of the present study was to evaluate in patients with acute lymphoblastic leukemia (ALL) the oxidative status and antioxidant defense and its involvement in the relapse of ALL. The plasmatic levels of malondialdehyde (MDA), advanced oxidation of protein products (AOPP) and reduced glutathione (GSH), and the plasmatic activities of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were determined in 34 patients newly-diagnosed with ALL and compared with 92 healthy subjects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…It is well known that overproduction of ROS such as superoxide radicals (O 2 •− ), hydrogen peroxide (H 2 O 2 ), and the highly reactive hydroxyl radicals (OH • ) leads to the oxidative damage of lipids, proteins, and DNA . If not repaired DNA damage may bring mutagenesis and cause the onset or the development of different types of cancers, high ROS level was particularly incriminated in the resistance to BCR/ABL kinase inhibitors established in experimental cell lines. Our study was conducted to comprehend the mechanisms of resistance to IM order to find therapeutic solutions that may help prevent a relapse from this drug in CML.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that overproduction of ROS such as superoxide radicals (O 2 •− ), hydrogen peroxide (H 2 O 2 ), and the highly reactive hydroxyl radicals (OH • ) leads to the oxidative damage of lipids, proteins, and DNA . If not repaired DNA damage may bring mutagenesis and cause the onset or the development of different types of cancers, high ROS level was particularly incriminated in the resistance to BCR/ABL kinase inhibitors established in experimental cell lines. Our study was conducted to comprehend the mechanisms of resistance to IM order to find therapeutic solutions that may help prevent a relapse from this drug in CML.…”
Section: Discussionmentioning
confidence: 99%
“…During this study total inhibitor capability (TAC) cut considerably all told growth tissue during a correlational statistics with MDA levels which can be explained with the ensuing result of the SFN conjugation with the intracellular thiols of the tumor cells, like GSH, leading to a decrease within the pool of cellular-SH teams, which is able to doubtless render cells additional at risk of aerophilous stress [47], Is in agreement with Sarban et al World Health Organization studied the inhibitor arms in patients with atrophic arthritis, they reported associate degree multiplied MDA concentration that is that the most potent marker of aerophilous stress and cut levels of TAC and inhibitor enzymes [48] [49].…”
Section: Ferreira First State Oliveira Et Al (2014) Additionallymentioning
confidence: 96%
“…Battisti et al evaluated the oxidative status and antioxidant defense of patients with ALL and found that CAT and SOD activities in the whole blood of patients with ALL were lower by different levels than those in the normal control group and that SOD activity was lowest in newly diagnosed patients [ 105 ]. However, Ben Mahmoud et al found that the plasmatic activities of CAT and SOD and the plasma levels of reduced GSH were elevated in patients with ALL and that SOD activity and GSH levels were substantially correlated with ALL relapse [ 108 ]. Nishiura et al found that serum levels of Mn-SOD in patients with ALL were substantially higher than those in normal controls, but as the disease subsided, serum levels of Mn-SOD decreased [ 109 ].…”
Section: Redox Regulation In Leukemiamentioning
confidence: 99%